Legal Position and Organisation of Independent Regulatory Authorities in Poland (Contemporary Central & East European Law, 2024)
The article discusses the emergence and role of independent regulatory bodies in Poland, which were not part of the country’s administrative law during the Second Republic (1918–1939) or the People’s Republic of Poland (1945–1989). These bodies began to develop in the 1990s, influenced by European Union regulations designed to foster an internal market. The article examines how Poland, transitioning to a democratic state with a market economy after 1989, restructured its administrative apparatus to incorporate these bodies.The concept of national regulatory authorities (NRAs) is explored, with a focus on their role in regulating specific sectors of the economy, such as infrastructure, financial services and competition protection. Regulatory authorities are defined as bodies that intervene in markets to promote competition, prevent monopolies and ensure the provision of essential public services. The article also addresses the flexibility in how EU law defines and shapes NRAs, allowing each Member State to adapt these bodies to its specific needs. The Polish legal system is analysed to identify whether a distinct ‘Polish model’ of an NRA exists, and this is compared to the approaches of other EU countries.